Do Low-Risk Patients With Dyspepsia Need a Gastroscopy? Use of Gastroscopy for Otherwise Healthy Patients With Dyspepsia. Issue 1 (5th July 2021) - Halasz, Jennifer B; Burak, Kelly W; Dowling, Shawn K; Murray, Brenna; Williams, Jennifer; Misra, Tarun; Veldhuyzen van Zanten, Sander J; Kaplan, Gilaad G; Swain, Mark; Novak, Kerri L
Abstract: Background: Choosing Wisely Canada (CWC) recommends not to perform gastroscopy for dyspepsia in otherwise healthy adults less than 55 years of age (2014). The aim of this study was to evaluate the use of gastroscopy in a young, healthy population with uncomplicated dyspepsia. Methods: A retrospective review of gastroscopies completed during 3-month periods in 2015, 2016, and 2017 identified all patients undergoing gastroscopy for the primary indication of dyspepsia. Low-risk patients for dyspepsia were defined as adults, aged 18 to 54 years without alarm symptoms, comorbidities and/or abnormal imaging findings or laboratory values. Gastroscopy and pathology reports were reviewed to identify clinically actionable findings. Clinical outcomes were followed to December 31, 2018 including gastroenterology referrals, emergency room visitation and hospitalization. Results: Among 1358 patients having a gastroscopy for dyspepsia, 480 (35%) were low-risk patients. Sixteen patients 3.3% (16/480) had a clinically actionable result found on gastroscopy or biopsy. No malignant lesions were detected. Low-risk patients were followed up for an average of 2.75 years, 8% (39/480) visited the emergency department (ED), 1% (3/480) of patients were admitted to hospital and 12% (59/480) of patients were re-referred for a dyspepsia-related concern. Interpretation: A high rate of low yield, high cost, invasive endoscopic investigations were performed in this population of otherwise healthy patients under age 55 years. These data suggest limited uptake of current recommendations against the routine use of gastroscopy to investigate dyspepsia.